Peta Jalan Wisata Religi Kota Surakarta - Retno Kusumastuti; Sultan Nadjamuddin (Badan Riset dan Inovasi Daerah Kota Surakarta, 2024)
Several Islamic kingdoms once developed in the city of Surakarta, including the Pajang kingdom, Mataram Islam, and Kasunanan Surakarta, leaving behind several historical buildings and objects that have great potential for tourist attraction. If it can be utilized, it will contribute quite a large regional income to the city, considering that the city of Surakarta does not have natural resources and depends on its revenues from the service and trade sectors. The remains of the buildings and historical objects in question can be packaged into cultural tourism and religious tourism. The number of religious tourism objects in the city of Surakarta exceeds the number of cultural tourism, so it has become the attention of the Surakarta City Government to prepare a road map for religious tourism in the city of Surakarta, using primary and secondary data collection methodology with descriptive analysis. Before creating a road map, the first step taken is to identify the potential for religious tourism using SWOT and TOWS analysis. It is hoped that after the potential identification has been prepared, it can become a policy reinforcement in compiling the Surakarta City Religious Tourism Road Map because it will be used by the Surakarta City Government as a guide for the development of Religious Tourism so that it is effective, efficient and targeted in its management.